Leadership in the context of social-political and religious development of ancient Egypt - Nestulya, Oleksiy; Nestulya, Svitlana (Національний технічний університет "Харківський політехнічний інститут", 2019)
The influence of the leadership management paradigm of class societies on the formation of mechanisms of exercising power of the rulers of Ancient Egypt is analysed. It is shown that the ancient Egyptian pharaohs, claiming the status of mediators between pagan gods and humans, and subsequently their divine origin, were unable to abandon the sanctified traditions and beliefs of the requirements for rulers as leaders. Therefore, with the unlimited power of the Oriental tyrants, they continued to be accountable to the pagan gods and men for the observance of the principles of humanity, justice, and care for their subordinates. They demonstrated their exceptional qualities and abilities that gave them not only a formal right to operate them, but also to exercise them on the basis of authority. The history of the Ancient Egypt is full of the examples when the rejection from these underlying principles had deplorable effects for the whole country. Therefore, pharaohs of the country had to return to their reconsidering.

Проаналізовано вплив лідерської управлінської парадигми докласових суспільств на становлення механізмів реалізації влади правителів Стародавнього Єгипту. Показано, що давньоєгипетські фараони, утверджуючи за собою статус посередників між богами й людьми, а згодом і своє божественне походження, не змогли відмовитися від освячених традиціями й віруваннями вимог до правителів як до лідерів. Відтак, маючи необмежену владу східних деспотів, продовжували нести відповідальність перед богами й людьми за дотримання в управлінні принципів гуманності, справедливості, піклування за своїх підлеглих. Вони демонстрували свої виключні якості й здібності, які давали їм не лише формальне право управляти ними, а й реалізовувати його на основі авторитету. Історія Стародавнього Єгипту переповнена прикладами коли відмова від цих засадничих принципів управління мала згубні для країни наслідки. Тому фараони країни вимушені були знову й знову повертатися до їхнього осмислення.
Лідерство в контексті суспільно-політичного та релігійного розвитку стародавнього Єгипту
Keywords: ruling; social responsibility; ruler; управління; соціальна відповідальність; правитель